Learning to Trust Our Teachers: Second Installment of the Special Issue "Skills, Values, and Beliefs for Today's Democratic Citizenship" - Thayer-Bacon, Barbara; Ellison, Scott (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
We have a friend who is a secondary teacher from China and she asked us a hard question. After a couple of years of taking courses about American education, where she read much of the current research and critical analysis of schools in the U.S., and after spending time observing in American schools and listening to Americans talk about their schools and teachers, Hongmei Peng asked one day, “Why do you Americans not trust your teachers?” How insightful for her to notice, and how intriguing it is to hear that we are obvious in our mistrust, and that people in other parts of the world may not feel the same way about their teachers. She further asked: “Why are you willing to send your children to be with teachers you do not trust?” Good question!